PT Solare Marketing Strategy to Penetrate Business Market - Putra, Dimas Prakoso; Aldianto, Leo (The Indonesian Journal of Business Administration, 2013)
PT Solare is a producer of solar home system and solar powered street lighting. The company was built on the foundation to help people in rural area to receive proper lighting using solar energy as the source of electricity power. To reach this goal PT Solare uses donor-based model where they would approach customers who would want to purchase SHS and donate it to the people who lived in rural areas. PT Solare decided to choose third party firm; CV Citra Surya Utama (CV CSU) as the sales agent that will offer the products to the government organizations, and let the business segment handled by PT Solare personally. In the reality PT Solare just relying on government order which came from CV CSU and neglect the business segment. Based on this situation PT Solare profitability became depended with CV CSU performance, as a result when the performance of CV CSU declined the profitability PT Solare would also declined. Even though the positive trend of solar powered street lighting sales has made the company able to survive in the midst of declining sales of SHS products, the reality is the sales of both products are still below the expectation. PT Solare needs to improve the sales condition so the company can grow and achieve its vision which is to become the top of mind brand in solar powered lighting product. Root cause analysis has determined that the main causes for the low sales of PT Solare are the lack of marketing value in the company culture, and the lack of promotion initiatives. Currently PT Solare just waits until there are orders from CV CSU or other client who directly contacted the company. To address this root causes, PT Solare needs a marketing strategy that will become guidelines in marketing to prevent the problem from reoccurring. This final project uses Internal External (IE) Matrix and Quantitative Strategic Planning Matrix (QSPM) to determine which growth strategy that PT Solare should pursue and evaluate and selects possible strategies that more relevant with PT Solare condition. The result from IE Matrix and QSPM analysis are that PT Solare needs to penetrate the existing market which is the neglected business segment, using existing product by bolstering the perception of product reliability. The recommended strategies to enhance the perception of product reliability through product trial, longer warranty and enhance and communicate the reliability of PT Solare service. The final project also includes the communication method that appropriate for PT Solare to approach the business market. The communication method also addresses the internalization of marketing strategy which is to communicate the marketing strategy to company internal employees. Internalization of marketing communication is necessary in order to weave marketing value in PT Solare culture.Â Keywords: Marketing strategy